Sperm Ubiquitination Correlation with Human Semen Quality - MR Sadeghi; A Shabani; H Zeraati; MA Akhondi; A Talebian; M Hodjat (Tehran University of Medical Sciences, 2008)
Background: Ubiquitin, an 8.5 kDa peptide that marks other proteins for proteasomal degradation, tags defective sperm during epididymal passage. Thus, sperm ubiquitination is a universal marker for sperm defects and can be used as a sperm function test. The objective of the present study was to examine the relationships between sperm ubiquitination and clinical semen parameters, using simplified immunofluorescence assays in order to establish ubiquitin as a biomarker of male infertility. Methods: Semen samples from 100 couples attending Avicenna Infertility Clinic, Tehran, Iran, were collected and analyzed according to WHO criteria. Each sample was washed and adjusted at 106 sperm/ml concentration. Sperm were coated on slides, using cytospin centrifugation and were fixed in buffered formaldehyde. Subsequently ubiquitinated spermatozoa were evaluated by direct immunofluorescence microscopy using FITC-labeled anti-ubiquitin antibodies. After counting at least 200 sperm per sample, while employing light microscopy, the percentage of ubiquitinated spermatozoa was recorded on the same fields through epifluorescence microscopy. Results: Negative correlations were obtained between sperm ubiquitination and sperm count (r=-0.278, P< 0.001), sperm concentration (r=-0.37, P< 0.001), viability (r=-0.407, P< 0.001), sperm morphology (r=-0.509, P< 0.001), rapid progressive motility (a) (r=-0.246, P< 0.001) and slow progressive motility (b) (r=-0.474, P< 0.001). There was a positive correlation between ubiquitinated sperm and the percentage of immotile spermatozoa (r=0.486, P< 0.000). Conclusion: Increased sperm ubiquitination is inversely associated with good semen quality parameters, supporting the use of ubiquitin as a biomarker for evaluation of human sperm quality.